2021
DOI: 10.3390/agriculture11121286
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex CRISPR/Cas9 Mutagenesis of BrVRN1 Delays Flowering Time in Chinese Cabbage (Brassica rapa L. ssp. pekinensis)

Abstract: The VERNALIZATION1 (VRN1) gene is a crucial transcriptional repressor involved in triggering the transition to flowering in response to prolonged cold. To develop Chinese cabbage (Brassica rapa L. ssp. pekinensis) plants with delayed flowering time, we designed a multiplex CRISPR/Cas9 platform that allows the co-expression of four sgRNAs targeting different regions of the endogenous BrVRN1 gene delivered via a single binary vector built using the Golden Gate cloning system. DNA sequencing analysis revealed sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…In this study, mutation of MsFTa1 via CRISPR/Cas9 gene editing resulted in tetra‐allelic homozygous mutant plants with delayed flowering and increased plant height and fresh and dry biomass compared to the control plants (Figures 2 , 4 ). The results of this study are consistent with prior findings on the manipulation of plant genes known to promote flowering in improved agronomic traits, yield and quality in soybean (Cai et al ., 2019 ; Xu et al ., 2021 ), M. truncatula (Tadege et al ., 2015 ), alfalfa (Lorenzo et al ., 2020 ), rice (Cui et al ., 2021 ; Liu et al ., 2021 ; Wu et al ., 2020 ; Zhang et al ., 2019 ), switchgrass (Gou et al ., 2019 ), Chinese cabbage (Hong et al ., 2021 ) and tomato (Rajendran et al ., 2021 ; Shalit et al ., 2009 ). Recently, the role of the FTa1 gene in alfalfa was confirmed by down‐regulating its expression through an artificial microRNA (amiRNA) (Lorenzo et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, mutation of MsFTa1 via CRISPR/Cas9 gene editing resulted in tetra‐allelic homozygous mutant plants with delayed flowering and increased plant height and fresh and dry biomass compared to the control plants (Figures 2 , 4 ). The results of this study are consistent with prior findings on the manipulation of plant genes known to promote flowering in improved agronomic traits, yield and quality in soybean (Cai et al ., 2019 ; Xu et al ., 2021 ), M. truncatula (Tadege et al ., 2015 ), alfalfa (Lorenzo et al ., 2020 ), rice (Cui et al ., 2021 ; Liu et al ., 2021 ; Wu et al ., 2020 ; Zhang et al ., 2019 ), switchgrass (Gou et al ., 2019 ), Chinese cabbage (Hong et al ., 2021 ) and tomato (Rajendran et al ., 2021 ; Shalit et al ., 2009 ). Recently, the role of the FTa1 gene in alfalfa was confirmed by down‐regulating its expression through an artificial microRNA (amiRNA) (Lorenzo et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the heading date of rice was delayed by fine‐tuning flowering time genes ( Ehd1 and Hd2 ) using CRISPR/Cas9, which resulted in prolonged vegetative growth period with improved yield potential for flexible cropping systems in diverse environments (Liu et al ., 2021 ; Wu et al ., 2020 ; Zhang et al ., 2019 ). Flowering time in Chinese cabbage ( Brassica rapa L.) was also delayed by targeting BrVRN1 using multiple guide RNAs (gRNAs) in the multiplex CRIPSPR/Cas9 construct to generate lines with different flowering times for crop improvement (Hong et al ., 2021 ). Similarly, CRISPR/Cas9 mutagenesis in soybean targeting two flowering genes ( GmFT2a and GmFT5a ) improved adaptability of soybean to different environments with desirable transgene‐free mutant lines (Cai et al ., 2018 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, genome editing in Chinese cabbage has been performed for different traits, such as FLOWERING LOCUS C (FLC) for early flowering, BrVRN1 gene for delayed flowering, and PR55/B gene for self-incompatibility [ 41–43 ]. Moreover, DNA-free (transgene-free) genome editing by targeting the vernalization determinant FRIGIDA and phytoene desaturase gene (FRI and PDS) genes has also been done to pave toward minimizing GMO legislation-related issues [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have reported modifying genes using CRISPR/Cas9 in B. rapa . These studies focused on genes involved in flowering time [ 12 ], leaf color transition [ 13 ], methylation of pectin [ 14 ], self-incompatibility [ 15 ], and circadian rhythms [ 16 ]. However, considering that the end goal of CRISPR/Cas9 GE is to obtain a transgene-free homozygous plant harboring a precise modification of a specific target gene, and the altered sequence and the resulting traits should be stably inherited, there is still a need for efficiency improvement and diversification of objectives in the CRISPR/Cas9 application for B. rapa .…”
Section: Introductionmentioning
confidence: 99%